IMPLEMENTASI PEMBELAJARAN MENGGUNAKAN LABORATORIUM VIRTUAL PADA MATERI CAHAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP - Dwi Ajeng Andini; Yennita Yennita; Zulhelmi Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to describe and find out the differences in cognitive learning outcomes in classes that apply learning using laboratorium virtuals, PhET Simulation and the Physics Classroom, as an experimental class compared to a class that applies conventional learning as a control class. The type of research used is quantitative with the Quasi Experimental research method and the Nonequivalent Post-test Control Group Design research design. This research was conducted at SMP N 42 Pekanbaru by using cognitive learning outcomes tests on the Light subject. The cognitive learning outcomes test consists of 20 multiple choice questions based on cognitive level according to Bloom's taxonomy revision. The data in this study were in the form of achievement scores of students' cognitive learning outcomes after being given treatment which were analyzed descriptively. Furthermore, differences in cognitive learning outcomes were analyzed using the SPSS version 25 application for inferential analysis. Based on the descriptive analysis and inferential analysis of the data, the cognitive learning outcomes of the experimental class students were 71.76, while the control class was 53.59. Thus it can be concluded that learning using laboratorium virtuals, PhET Simulation and the Physics Classroom, has an influence on the cognitive learning outcomes of students at SMP N 42 Pekanbaru.Key Words: Virtual laboratory, PhET Simulation, the Physics Classroom, Cognitive Learning Outcomes, Light Subject